Supplementation of vitamins C, E and its combination on paraquat-intoxicated rats: effects on some biochemical and markers of oxidative stress parameters - Akinloye O.A., Adamson I., Ademuyiwa.O, Arowolo T.A (Journal of Applied Pharmaceutical Science)
Paraquat (PQ) is a toxic chemical that is widely used as an herbicide in developing countries. It has been described as a major suicide agent, thus leading to its ban or restriction in use by Environmental Protection Agency in some countries. There is no known chelating agent or antidote for PQ. This study investigated protective effects of antioxidant vitamins C, E and its combination in both pre-treatments and post-treatments. Pre-treatment of rats with vitamins C, E and C+E gave survival rates of 40%, 20%and 20% respectively while post-treatment gave 80%, 20% and 20% respectively when lethal dose (150mg/Kg) of PQ was administered. However, when sub-lethal dose (75mg/Kg) was administered, biochemical investigations revealed a significant (p
Keywords: Vitamins C and E, paraquat, oxidative stress, rats.